Analysis of Transmission Lightning Arrester Locations Using Tflash - M. I. Jambak; Z. Nawawi; R.F. Kurnia; Z. Buntat; M. A. B. Sidik; Y. Z. Arief; A. A. Wahab; Z. Ramli; M. E. Ramly (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2016)
Tropical countries with extensive lightning activity, such as Malaysia, encounter numerous problems on their electrical transmission and distribution systems. Many overhead lines trip because of back flashover of lightning and shielding failures of the grounding system. To overcome the problem and improve transmission line performance, a detailed lightning study is required to analyse the corresponding lines and determine the best location for transmission line arrester (TLA) installation. We used TFlash to analyse a TLA installation on a 132-kV SSWW-BBST overhead transmission line system located in Selangor, Malaysia. Based on the results, the installation of the TLA at the optimum quantity and at appropriate towers have reduced the number of lines that trip.